BOOK METHODOLOGY (SCIENTIFIC AND RESEARCH ASPECTS) - JELNIKOVAS, MICHAILAS (Knygotyra, 2011)
Upon performing a critical analysis of the current key general scientific methodology concepts in Russian and foreign literature, the following integrated concept could be suggested: scientific methodology is a form of scientific knowledge about scientific cognition principles, methods, means and processes as well is a form of development, organisation and implementation of such a cognition. The unity of both these forms constitutes the system of methodology knowledge or general methodology, which (along with science and philosophy) is the third fundamental form of consciousness. The book methodology has its own system of concepts, its own object, subject, structure and composition as well as its own place among other disciplines and its own clearly defined boundaries. All the above facts indicate that a new discipline is emerging in the book science. This discipline will have a vital role while obtaining new knowledge about the book, forming the book theory and developing the common book science. The methodological book cognition instrument is a system of intermingled book cognition principles, methods and means, which are also related with to levels of cognition. Cognition principles, as a high concept idea or cognition rules, show the directions, character, level and methods of the cognition process. The following principles can be classified according to cognition levels: principles of monitoring, reconstitution and integrity at the empirical level; principles of logical determination, systematicity, functionality and historicity at the theoretical level. The key elements of the methodological instrument of book cognition are methods. Methods are classified according to two levels – theoretical and empirical – of scientific cognition. Methods of the first level include visual inspection and empirical explanation, whereas the second level includes formal logical, systemic, functional, sociological, historical and other methods. Scientific methods of book cognition as elements of the methodological instrument are not a mere set of methods. They are a systemic formation predetermined by the system of cognition principles on the one hand, and on the other hand – by a system of elements, aspects and phenomena for the cognition of which these methods are designed. However, their efficiency can be ensured only through integration with book cognition means. All means of scientific cognition can be divided into three groups: 1) means designed for a specific aim; 2) production means designed for other purposes but used as means of cognition; 3) items or phenomena of the surrounding world, used for cognition. The system of book cognition principles, methods and means, harmonised in terms of hierarchy, structure and functions, constitutes a methodological book cognition instrument. The methodological book analysis comprises three procedures: construction of the cognition process, preparation and inclusion of the methodological instrument, and reception of knowledge about the book. The structure of the book methodological analysis (a scheme of the movement of cognition levels) can be general (based on general aims) and specific (based on a subject specific features). The general structure of the methodology of book analysis can serve as a model while developing special structures predetermined by the specificity of the subject under analysis.